Molecular Docking Analysis of Anti-malarial Compounds as Plasmepsin IV Inhibitor from Targeted Indonesian Medicinal Plants - Arthur Hariyanto Prakoso; Muhammad Habiburrohman; Wilda Nur Rohmatillah; Bawon Triatmoko; Ari Satia Nugraha (Future Science)
Malaria is one of the major causes of death in tropical and sub-tropical countries, caused by the infection of the protozoan parasite (Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, and Plasmodium knowlesi). As the prevalence of parasite drug-resistant strains increasing, alternative medicine to eliminate malaria is needed. In this study, a molecular docking protocol was employed to predict and select natural compounds from Indonesian medicinal plants as an antimalarial drug candidate. The docking protocol was validated by the RMSD value of crystal versus docking calculation. From 43 species of plants, 238 total compounds were collected and docked into Plasmepsin IV (PMIV) enzyme which plays a role in the nutrition uptake of Plasmodium in human blood circulation. This enzyme was collected from a protein database with codename 5I70. The protocol was produced an acceptable RMSD value of 1.435 ?. The docking experiment resulted in AM202 (Cassiamin B) from Cassia siamea as the best potent Plasmepsin IV inhibitor. This compound has the potential candidate for future anti-malarial drugs. Cassiamin B had an affinity value of -11.2 kcal/mol which was higher than PMIV’s native ligand (-3.8 kcal/mol).